Founder–inventors and their investors: Spurring firm survival and growth - Haeussler, Carolin; Hennicke, Maria; Mueller, Elisabeth (Strategic Entrepreneurship Journal, 2019)
Abstract Research Summary Drawing on insights from resource orchestration literature and the competence‐based perspective, we argue that founders involved in inventive activities display firm‐idiosyncratic founder–inventor competences critical to the firm's performance. This effect is enhanced by venture capital investors. To test our hypotheses, we use panel data from 1,498 firms. Controlling for founders' technical skills, our results reveal that founder involvement in R&D increases firm survival and growth. Furthermore, venture capitalists leverage founders' engagement in inventive activity to achieve even higher growth. Our findings imply that continuous application of founder–inventor competences serves to catalyze effective resource orchestration and strengthen new venture performance. Managerial Summary The role of founders and founder competences is critical as firms progress along their life cycles, whereby founders face decisions about which tasks deserve their attention and which ones they can delegate to their employees, middle‐management, and/or new hires. One key strategic choice for founders is whether to engage in inventive activities themselves and remain engaged. Based on a large firm dataset, we find that founders' inventive activities spur survival and growth. Furthermore, venture capital investors leverage the effect on growth because they often bring in their own industry expertise, turn attention to the core capabilities, and revitalize the top management team. These investor activities enable founders to focus their attention on areas in which their involvement best supports the firm's performance, namely inventive activities.